Outcomes of Trabeculectomy with Mitomycin C in Glaucoma Patients: A Study on the Mean Change in Intraocular Pressure in 200 Patients - Iftikhar Ul Haq Tareen, Ghazala Tabassum, Muhammad Rafiq, Mohammad Afzal Khan, Anwar Ul Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to evaluate the outcomes of trabeculectomy with Mitomycin C (MMC) in terms of mean change in intraocular pressure (IOP) in 200 glaucoma patients. Methods: A cohort of 200 glaucoma patients undergoing trabeculectomy with MMC was analyzed. Preoperative and postoperative IOP measurements were taken at intervals (1 month, 3 months, 6 months, and 12 months). Demographic variables, surgical complications, and postoperative interventions were also recorded. Results: The mean preoperative IOP was 26.4 mmHg, which decreased significantly to 12.3 mmHg at 12 months post-surgery. The success rate in achieving target IOP (< 21 mmHg) was 87%. The incidence of postoperative complications such as hypotony, infection, and bleb leaks was low. Conclusion: Trabeculectomy with MMC is highly effective in reducing IOP in glaucoma patients, with a significant mean change in IOP from preoperative to postoperative stages. MMC plays a key role in improving surgical success by preventing scarring and bleb failure. Keywords: Trabeculectomy, Mitomycin C, intraocular pressure, glaucoma, surgical outcomes, postoperative complications.